THE PETROLOGY CHARACTERISTIC OF GRANITOID ROCK BASED ON GEOCHEMICAL ANALYSIS OF BAJAU CAPE COAST AND ITS SURROUNDING, WEST KALIMANTAN - Noor C.D. Aryanto; E. Suparka (BULLETIN OF THE MARINE GEOLOGY, 2013)
The aim of this study is to identify of petrology characteristic based on geochemical analysis in order to know the granitoid rock type. Administratively, the study area is in the City and District of Singkawang, West Kalimantan Province, at coordinate 108Â°48'30â€ - 109Â°1'30â€ E and 0Â°40'30â€ - 0Â°54'30â€ N and, situated Â± 145 km to the north of Pontianak City. The outcrop of granitoid along Bajau Cape coast and its surrounding, had been analyzed petrographically and geochemically using AAS method. Based on analysis of five samples show that the ratio mole of Al2O3/(CaO+Na2O +K2O) > 1 ranged between 1.12 and 1.7, while the rest of three samples are moderately aluminous, with a ratio value between 0.5 and 1.0. The ratio between K2O and (K2O+Na2O+CaO) ranges 0.07 to 0.55 (moderate) that forms alkali feldspar normative ranges from 3.8 to 15.89 wt%. This ratio shows that granite alkali feldspar is classified to be calc-alkaline series. Petrographically, this rock is porfiritic texture, hollocrystalline, granular hypodiomorphic and biotite present as phenocryst, yellowish brown, euhedral, thin and platy. The content of oxides element (Na2O and MgO) tend to decrease, whereas of other oxides elements, namely Al2O3, TiO2, K2O, FeO and CaO increased, parallel with the raising of SiO2. Therefore, the Singkawang Granitoid can be grouped as alkali feldspar granite, syeno-granite and quartz monzonite. Keywords: petrography, geochemstry, major elements, calc-alcaline affinity, granitoid type and Bajau Coast, West Kalimantan. Penelitian ini bertujuan untuk mengidentifikasi karakteristik petrologi, berdasarkan analisa geokimia sehingga jenis batuan granitoidnya dikenali. Secara administratif, daerah penelitian termasuk ke dalam Kota dan Kabupaten Singkawang, Provinsi Kalimantan Barat, pada koordinat 108Â°48'30â€ - 109Â°1'30â€ BT and 0Â°40'30â€ - 0Â°54'30â€ LU dan terletak Â± 145 km, arah utara dari Kota Pontianak. Singkapan batuan granitoid sepanjang pantai Tanjung Bajau dan sekitarnya telah dianalisis secara petrografi dan geokimia dengan menggunakan AAS. Berdasarkan 5 contoh yang dianalisa menunjukan perbandingan mol Al2O3/(CaO+Na2O +K2O) > 1, yakni berkisar antara 1,12-1,7, sedangkan 3 contoh sisanya bersifat peraluminus sedang, dengan nilai ratio antara 0.5-1.0. Perbandingan antara K2O dan (K2O+Na2O+CaO) berkisar antara 0,07-0,55 (sedang) yang membentuk alkali normatif feldspar berkisar 3,84 â€“ 15,89% (berat). Perbandingan tersebut menunjukan batuan Granit alkali feldspar yang tergolong dalam seri batuan kalk-alkali. Secara petrografi, batuan tersebut menunjukkan tekstur porfiritik, holokristalin, hipidiomorfik granular dengan biotit hadir sebagai fenokris, coklat kekuningan, euhedral, pipih dan sedikit berlembar. Kandungan unsur oksida (Na2O dan MgO) cenderung mengalami penurunan, sedangkan unsur oksida lainnya, yaitu Al2O3, TiO2, K2O, FeO dan CaO mengalami kenaikan sejalan dengan makin bertambahnya SiO2. Maka dengan demikian Granitoid Singkawang dapat dikelompokan menjadi granit alkali feldspar, syenit-granit dan kuarsa-monsonit. Kata kunci: Petrografi, geokimia, senyawa utama, afinitas kalk-alkalin, batuan granitoid dan Pantai Bajau, Kalimantan Barat.